Integrating E-Storybook and Print Picture Book in Project-Based Learning Model to Enhance Students’ Narrative Reading Comprehension with Different Learning Styles: Mengintegrasikan E-Storybook dan Buku Gambar Cetak dalam Model Pembelajaran Berbasis Proyek untuk Meningkatkan Pemahaman Membaca Naratif Siswa dengan Gaya Belajar yang Berbeda - Sri Rahayu, Yayu (International Journal of English Language and Pedagogy, 2025)
This study aims at finding out whether there is a significant difference between reading comprehension scores among students with different learning styles; visual auditory, and kinaesthetic of the second semester students of English language education study program in one private university in Bandung Regency. This study used quantitative method and causal-comparative design. The instruments of this study included learning style questionnaire and reading comprehension test. Further, it used independent sample t-test to analyze the data from learning styles questionnaire, and reading and reading comprehension scores. Findings of the result reveal that there was significant difference between students’ reading comprehension scores based on there groups’ learning styles: visual, auditory and kinaesthetic . The result shows that that using e-storybooks in Project-Based Learning (PjBL) helped improve the reading comprehension of students with different learning styles: Visual, Auditory, and Kinesthetic.For Visual learners, the use of e-storybooks led to a significant improvement, with their average score increasing from 29.23 in the pre-test to 67.46 in the post-test. The use of print picture books in Project-Based Learning (PjBL) proved to be highly effective in improving the reading comprehension of students with different learning styles. For Visual learners, there was a significant improvement in reading comprehension, with the mean score increasing from 28.13 in the pre-test to 84.63 in the post-tes